Proposed content in health instruction for the second year high school - Salalima, Nelia R. 1939- (s.n.], 1968)
The documentary analysis method was used in the study in an attempt to propose the content for health instruction based on established needs and interests of second year high school students. The proposed content was presented in three units namely: protecting yourself against personal health hazards, protecting yourself against community health hazards, and safeguarding your emotional health.